Enhanced TrkA signaling impairs basal forebrain-dependent behavior - Calvo-Enrique, Laura; Lisa, Silvia; Vicente-García, Cristina; Deogracias, Ruben; Arévalo, Juan Carlos (Frontiers in Molecular Neuroscience, 2023)
Basal forebrain cholinergic neurons (BFCNs) modulate cognitive functions such as attention, learning and memory. The NGF/TrkA pathway plays an important role in the development and function of BFCNs, although two mouse models conditionally deleting TrkA expression in the central nervous system (CNS) have shown contradictory results. To shed light into this discrepancy, we used a mouse model with a gain-of-function in TrkA receptor signaling. Our results indicate that enhanced TrkA signaling did not alter hippocampal cholinergic innervation, general locomotion or anxiety-related behaviors, but it increases ChAT expression, the number of cholinergic neurons at early postnatal stages and, mutant mice showed impaired motor learning and memory functions. These data demonstrate that proper functioning of the cholinergic system in CNS requires a balanced NGF/TrkA signaling.